Climate control in the feeding area for Girolando cows: Effects on environmental and production variables - Lainny J. M. P. e Sousa; Roberta Passini; Eduardo A. de Almeida; Alliny das G. Amaral (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT High-production cows require facilities providing comfortable environments to enhance production efficiency and sustain milk quality. This study evaluated the impact of climatizing the feeding area post-morning and afternoon milking on environmental variables, thermal comfort indices, and the yield and quality of milk in lactating Girolando cows. The experiment followed a 4 × 4 Latin square design with four treatments across four experimental periods, using four cows per treatment. The post-milking climate control treatments included: shading; shading + ventilation; shading + ventilation + shower; and an evaporative adiabatic cooling system. The evaporative adiabatic cooling system proved most effective in maintaining thermal conditions near the comfort level for dairy cows, as indicated by lower thermal comfort indices. This system also enhanced morning and overall milk production. However, the climate control systems did not significantly affect the contents of protein, fat, or lactose in the milk.